Administering an additional prostaglandin F2α injection to Bos indicus beef cows during a treatment regimen for fixed-time artificial insemination - Noronha, Isabella M. [UNESP]; Cooke, Reinaldo F.; Martins, Cícero F.G.; Oliveira Filho, Ramiro V.; Pohler, Ky G.; Vasconcelos, José L.M. [UNESP] (Elsevier, 2020)
Two experiments were conducted to evaluate if an additional prostaglandin F2α (PG) injection during an estradiol-based estrous synchronization treatment regimen affects pregnancy rates resulting from fixed-time artificial insemination (FTAI) in Nelore cows. In Experiment 1, 1039 cows were administered estradiol benzoate and an intravaginal progesterone releasing device (CIDR) on d -11, an injection of PG on d -4, with CIDR removal and administration of estradiol cypionate and eCG occurring on d -2, and FTAI on d 0. Cows were administered an additional injection of PG (PG2) or saline (PG1) on d -2. Percentage pregnancy per FTAI on d 30 was greater (P = 0.01) in cows of the PG2 than PG1 group (54.5 % and 46.6 %, respectively). In Experiment 2, there was use of the same treatment regimen for estrous synchronization of 934 cows as that for Experiment 1 followed by FTAI, with there being diagnosis of whether cows had or did not have a corpus luteum on d -4. Response to estrous synchronization, largest follicle diameter at FTAI, and pregnancy per FTAI were greater (P ≤ 0.05) in cows of the PG2 than PG1 group with a body condition score (BCS) < 5.0 at FTAI (81.2 % and 72.6 %, 11.9 and 11.2 mm, 55.5 and 45.6 %; respectively). These treatment responses did not differ (P ≥ 0.18) in cows with BCS ≥ 5.0. Collectively, results indicate that treatment with PG2 increased pregnancy per FTAI in B. indicus cows deficient in body energy reserves, by enhancing follicle development and estrous synchronization response.
Keywords: Beef cows; Fixed-time artificial insemination; Pregnancy; Prostaglandin F2α